EFFECTIVENESS OF EARLY CATARACT REMOVAL SURGERY IN ACUTE ANGLE CLOSURE (Vietnam Journal of Community Medicine, 2022)
Objectives: To evaluate the effectiveness and safety of early cataract removal in cases of acute angle closure and primary angle closure.Methods: A prospective surgical intervention study without a control group implemented for 50 eyes of 40 patients with acute angle closure or primary angle closure with high intraocular pressure >21mmHg, anterior chamber angle still opened >1800, early cataracts were performed phacoemulsification with artificial intraocular lens implantation. Variables including intraocular pressure, visual acuity, amount of antihypertensive medication, anterior chamber angle opening status and intraoperative and postoperative complications were recorded and followed for 1 week, 4 weeks, 3 months, 6, and 12 months.Results: The visual acuity improved from 0.34 ± 0.18 to 0.06 ± 0.04 LogMAR (p
Keywords: Acute angle closure, primary angle closure glaucoma.